Mister meddle's mischief - Blyton, Enid; Catchpole, Diana (Award Publications Worksop, England, 2014)
Mister Meddle's Mischief follows the comical adventures of Mister Meddle, a well-meaning but clumsy character whose attempts to help others often lead to chaos and unintended consequences.